2021
DOI: 10.1097/mcg.0000000000001535
|View full text |Cite
|
Sign up to set email alerts
|

A Quality Improvement Initiative Is Associated With Reduced Time to Administer Biologics and Small Molecules and Emergency Room Visits in Inflammatory Bowel Disease

Abstract: Background: Delays in biologic or small molecule medication administration are associated with increased adverse events, hospitalization, and surgery in inflammatory bowel disease (IBD). We evaluated the impact of a quality improvement (QI) intervention on the time to administration of biologics or small molecules (TABS) in IBD. Methods: Data were retrospectively extracted for IBD patients prescribed biologics or small molecules from a convenience sample of providers participating in an accredited QI educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…After the elimination of duplicates, 1515 titles and abstracts were evaluated for eligibility; 1385 were excluded. On review of 148 full texts, 100 studies were included: 35 peer reviewed publications [ 16 50 ] and 65 conference abstracts [ 51 – 115 ]. Fig 1 details reasons for rejection.…”
Section: Resultsmentioning
confidence: 99%
“…After the elimination of duplicates, 1515 titles and abstracts were evaluated for eligibility; 1385 were excluded. On review of 148 full texts, 100 studies were included: 35 peer reviewed publications [ 16 50 ] and 65 conference abstracts [ 51 – 115 ]. Fig 1 details reasons for rejection.…”
Section: Resultsmentioning
confidence: 99%
“… 19 A quality improvement initiative within 18 adult IBD providers aimed at improving time-to-biologic- and small-molecule administration found that the insurance approval process step was not improved and actually lengthened over time despite their shortening time to medication administration by 4 days through streamlined internal processes. 20 Within the pediatric study, they examined the impact of medication delays on IBD-related healthcare utilization within 6 months from the delay, and those who required prior authorization had a 13% (95% CI: 2.5–23.4) increase in healthcare utilization after adjusting for demographics and disease-severity characteristics. 18 …”
Section: Barriers To Care For Patients With Ibdmentioning
confidence: 99%
“…Physicians in private practice had greater than 75% compliance with every quality measure, while those in academic centers had 35%–100% compliance, with bone loss and vaccinations scoring lowest. 7 Battat et al 8 and Sapir et al 9 implemented QI-focused CME utilizing audit-feedback sessions to identify performance gaps in implementing IBD quality measures. 8 , 9 This led to addressing barriers to compliance and strategies to overcome them.…”
mentioning
confidence: 99%
“… 7 Battat et al 8 and Sapir et al 9 implemented QI-focused CME utilizing audit-feedback sessions to identify performance gaps in implementing IBD quality measures. 8 , 9 This led to addressing barriers to compliance and strategies to overcome them. In Battat’s study, this was the first part of 3 components.…”
mentioning
confidence: 99%
See 1 more Smart Citation